2023
DOI: 10.1038/s41467-023-37578-7
|View full text |Cite
|
Sign up to set email alerts
|

The m6A reader YTHDC1 and the RNA helicase DDX5 control the production of rhabdomyosarcoma-enriched circRNAs

Abstract: N6-Methyladenosine (m6A) is well-known for controlling different processes of linear RNA metabolism. Conversely, its role in the biogenesis and function of circular RNAs (circRNAs) is still poorly understood. Here, we characterize circRNA expression in the pathological context of rhabdomyosarcoma (RMS), observing a global increase when compared to wild-type myoblasts. For a set of circRNAs, such an increase is due to the raised expression of the m6A machinery, which we also find to control the proliferation ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Recent new publications further support the notion that DDX5 is a critical biomarker and target in specialized rare cancers. This includes (but may not be limited to) neuroblastoma [ 119 ], osteosarcoma [ 120 , 121 ], rhabdomyosarcoma (RMS) [ 122 , 123 ] and myeloproliferative neoplasms (MPN) [ 124 ]. These studies further demonstrate the advantage of using DDX5 as a target for anticancer drug development, since there are many special programs and mechanisms from the FDA and NIH to promote rare cancer drug development and commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Recent new publications further support the notion that DDX5 is a critical biomarker and target in specialized rare cancers. This includes (but may not be limited to) neuroblastoma [ 119 ], osteosarcoma [ 120 , 121 ], rhabdomyosarcoma (RMS) [ 122 , 123 ] and myeloproliferative neoplasms (MPN) [ 124 ]. These studies further demonstrate the advantage of using DDX5 as a target for anticancer drug development, since there are many special programs and mechanisms from the FDA and NIH to promote rare cancer drug development and commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we found that DDX5 interacted not only with METTL3 but also with METTL14 to form a stable complex. Although a previous study showed that DDX5 worked as a mediator of the back-splicing reaction and as a co-factor of the m6A regulatory network (Dattilo et al, 2023 ), our data provided the first piece of evidence showing that RNA helicases regulate mRNA m6A modification by forming a stable m6A methyltransferase writer complex. Unlike DDX46, which inhibits innate immunity by entrapping m6A-demethylated antiviral transcripts in the nucleus (Zheng et al, 2017 ), DDX5 suppresses bacterial-induced inflammation by regulating the building of an mRNA m6A ‘writer’.…”
Section: Discussionmentioning
confidence: 59%
“…RNA analyses were carried out as described by ref. 52 . Oligonucleotides used for this study are listed in Supplementary Data 4 .…”
Section: Methodsmentioning
confidence: 99%